Oral manifestations in patients with anorexia and bulimia nervosa: a systematic review - Garbin, Cléa Adas Saliba [UNESP] (2019)
Aim: To carry out a systematic review based on the analysis of national and international publications in the scientific literature about the occurrence of oral manifestations in patients with anorexia and bulimia nervosa. Methods: We searched for evidence in the PubMed, Scopus, Web of Science, VHL Regional Portal, and Embase databases. We included case–control studies that analyzed oral manifestations such as dental caries, periodontitis, malocclusion, dental erosion, and soft-tissue lesions in individuals of both sexes with anorexia and bulimia nervosa. The method for quality assessment of each study was according to Downs and Black criteria. Results: We identified 1958 studies. Excluding repeated studies, 1045 papers remained. We removed those that did not approach the theme proposed and applied the exclusion criteria, leaving 66 surveys. We analyzed abstracts in duplicate, excluding those with inconsistent results, or which were biased or unclear, and those that did not meet the standards established. Conclusion: The final number of studies was six; all of them dealt with the question of oral manifestations found in patients with anorexia and bulimia nervosa, and presented validity and consistency in their methodological structure and results.